ISOLATION OF CHEMICAL ACTIVE COMPOUNDS ANTIOXIDANT FROM ETHYL ACETATE FRACTION OF BETEL LEAF FOREST (Piper aduncum L.) - Batan, Alfrida; Daniel, Daniel; Simanjuntak, Partomuan (Jurusan Kimia FMIPA UNMUL, 2018)
Research about the isolation of chemical active compounds antioxidants from ethyl acetate fraction of betel leaf forest (Piper aduncum L.) have been done. This research aimed to determine the type of secondary metabolites that contained in ethyl acetate fraction and the value of antioxidant activity as well as the structure that contained in ethyl acetate fraction. The test results of phytochemical showed that the secondary metabolites in ethanol extract are alkaloids, steroids and triterpenoids. The inhibitory concentration 50% (IC50) value that shown in the fraction Piper aduncum ethyl acetate-4-3 (PAEA-4-3) is 132.84 ppm. Fraction of PAEA-4-3 that have high levels of antioxidant activity was analyzed using a spectrophotometer Ultra Violet-Visible (UV-Vis), Infrared Fourier-Transform (FTIR) and Nuclear Magnetic Resonance (NMR) proton and carbon. The result analysis of PAEA-4-3 isolates showed the compound as 2,3-dimethoxy-metilanaoksi-benzene.